In‐hospital worsening heart failure. (3rd August 2015) - Butler, Javed; Gheorghiade, Mihai; Kelkar, Anita; Fonarow, Gregg C.; Anker, Stefan; Greene, Stephen J.; Papadimitriou, Lampros; Collins, Sean; Ruschitzka, Frank; Yancy, Clyde W.; Teerlink, John R.; Adams, Kirkwood; et al.
Abstract : Acute worsening heart failure (WHF) is seen in a sizable portion of patients hospitalized for heart failure, and is increasingly being recognized as an entity that is associated with an adverse in‐hospital course. WHF is generally defined as worsening heart failure symptoms and signs requiring an intensification of therapy, and is reported to be seen in anywhere from 5% to 42% of heart failure admissions. It is difficult to ascertain the exact epidemiology of WHF due to varying definitions used in the literature. Studies indicate that WHF cannot be precisely predicted on the basis of baseline variables assessed at the time of admission. Recent data suggest that some experimental therapies may reduce the risk of development of WHF among hospitalized heart failure patients, and this is associated with a reduction in risk of subsequent post‐discharge cardiovascular mortality. In this respect, WHF holds promise as a endpoint for acute heart failure clinical trials to better elucidate the benefit of targeted novel therapies. Better understanding of the pathophysiology and a consensus on the definition of WHF will further improve our epidemiological and clinical understanding of this entity.